2017
DOI: 10.5267/j.ijiec.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization of surface roughness and tool vibration in CNC turning of Aluminum alloy using hybrid RSM-WPCA methodology

Abstract: This paper suggests an advanced hybrid multi output optimization technique by applying weighted principal component analysis (WPCA) incorporated with response surface methodology (RSM). This investigation has been carried out through a case study in CNC turning of Aluminum alloy 63400 for surface roughness (Ra) and tool vibration (db) optimization. Primarily, input parameters such as spindle speed (N), feed rate (S) and depth of cut (t) are designed for experiment by using RSM Box-Behnken methodology. The alum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
1
15
0
2
Order By: Relevance
“…Cutting power and Ra. Sahoo et al (2017) selected response surface methodology (RSM) to design an experiment of DOC, FR and CS on aluminum alloy 63400 for optimizing variation of tool and Ra. Workpieces were machined by using carbide tool in dry environment.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Cutting power and Ra. Sahoo et al (2017) selected response surface methodology (RSM) to design an experiment of DOC, FR and CS on aluminum alloy 63400 for optimizing variation of tool and Ra. Workpieces were machined by using carbide tool in dry environment.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Their experimental results showed that increasing cutting speed leads to decreasing surface roughness, and this has been interpreted as a result of the decreasing built-up edge formation tendency which is a consequence of the increase the cutting speed. Sahoo et al [12] carried out statistical modeling using both the weighted principal component analysis and RSM in order to investigate the effect of the process parameters on the surface roughness and tool vibration in CNC turning of aluminum alloy 63400. They concluded that the interaction effects of the spindle speed (Vc) and feed rate (f) were significant for the model in the case of tool vibration.…”
Section: Introductionmentioning
confidence: 99%
“…Priyabrata Sahoo et al (2017) developed an empirical model using weighted principal component analysis (WPCA) and response surface methodology (RSM) to investigate the effect of feed rate, depth of cut and spindle speed on tool vibration and surface roughness on Aluminum Alloy using coated carbide tool inserts in dry environment for turning process. Box-Behnken methodology was employed to RSM model was used to optimize the response that is influenced by various process parameters and WPCA was employed to achieve the better combination of process parameters to obtain optimum machining conditions.…”
Section: Application Of Taguchi Methods In Manufacturing Processesmentioning
confidence: 99%